PENINGKATAN PENGETAHUAN DAN KEMAMPUAN PENGAPLIKASIAN PENGELOLAAN SAMPAH PADA MASYARAKAT DUSUN TEGALTANDAN BANGUNTAPAN BANTUL - Rokhmayanti , Rokhmayanti; Alghozi, Umar Faruq; Badri, Mohammad Zain; Wibowo, Rena Anjeli; Farzanah, Atikah; Sya’baniah, Putri Rahayu; Azzahra, Losa Rarafatmi; Martini, Titim; Hastuti, Siti Kurnia Widi; Astuti, Fardhiasih Dwi (P3M Universitas Aisyiyah Surakarta, 2025)
Garbage is a problem for people in both urban and rural areas. Unmanaged garbage can adversely affect public health. This community service aims to handle organic waste problems that have a role in social, environmental, and health impacts. Community service on organic waste management was carried out in Tegaltandan with lectures and practice methods in an effort to increase community knowledge and understanding of household organic waste management. Pre-test and post-test were conducted by distributing questionnaires to increase community knowledge about the meaning of organic waste, grouping types of organic waste, and organic waste management. The result of this service is the increasing ability of the community to manage organic waste. This increased ability can trigger the community to be more consistent in carrying out waste management in order to create a healthy environment.